Edukasi Kesehatan tentang Pencegahan Gout Arthritis di Desa Bangga Kabupaten Sigi - Nur Febrianti; Yulta Kadang; Iman Hikam (PT.Mantaya Idea Batara, 2021)
Tri dharma of higher education is the obligation of lecturers, and one of them is community service. This service raised the theme of health education on the prevention of gout arthritis. Previously, a Health screening was carried out with the Sheep Indonesia Foundation that the problem found in Proud Village was gout arthritis. Proud Village is a remote area in Sigi Regency. The purpose of this community service is to increase public knowledge about the prevention of gouty arthritis. The method of implementing community service with direct counseling techniques to the community with media flip chart and leaflet. The results of the service, the community is very enthusiastic to listen to the material. Previously, many residents did not know about gout arthritis. This is reflected in the many questions asked regarding the disease. In the evaluation session, the community was given questions and on average the community could answer correctly according to the material provided. The conclusion of community service activities has been carried out smoothly. The community response is very good and it is hoped that the community can prevent the occurrence of gout arthritis, and this community service activity can be carried out regularly